Therapeutic selection for abnormal uterine bleeding with ovulatory dysfunction: a cross-sectional study in Chinese women - Xiaoyue Zhao; Min Luo; Qinjie Tian (Future Science OA)
Objective To investigate the therapeutic selection of abnormal uterine bleeding with ovulatory dysfunction (AUB-O) among Chinese women and analyze the impact of various factors.Methods This was a cross-sectional study involving 3527 patients with AUB-O diagnosed by local doctor between 14 and 55 years old. Questionnaire compiled according to the Chinese AUB-O treatment guidelines was used to collect the demographic and therapeutic information.Results The patients were divided into the juvenile group, the reproductive group, and the senior group. The results showed that irregular menstruation (37.6–46.3%), dysmenorrhea (29.9–44.4%), and heavy menstrual bleeding (16.7–32.2%) were the main symptoms in Chinese AUB-O patients. Most of the patients chose to seek help in the Department of General Gynecology (78.6–90.7%). Among the therapeutic options, combined oral contraceptives (COCs) met the treatment expectations with high acceptance among patients (36.6%-52.2%).Conclusion This study underscores the crucial need to fortify the endocrine diagnostic proficiency of doctors within the Department of General Gynecology. Furthermore, it also indicates that implementing clinical medication education programs for patients could facilitate their correct selection of appropriate therapeutic strategies for AUB-O.